Identification and characterization of Faecalibacterium prophages rich in diversity-generating retroelements - Anastasia Gulyaeva; Lei Liu; Sanzhima Garmaeva; Marloes Kruk; Rinse K. Weersma; Hermie J. M. Harmsen; Alexandra Zhernakova (Microbiology Spectrum)
ABSTRACT Metagenomics has revealed the incredible diversity of phages within the human gut. However, very few of these phages have been subjected to in-depth experimental characterization. One promising method of obtaining novel phages for experimental characterization is through induction of the prophages integrated into the genomes of cultured gut bacteria. Here, we developed a bioinformatic approach to prophage identification that builds on prophage genomic properties, existing prophage-detecting software, and publicly available virome sequencing data. We applied our approach to 22 strains of bacteria belonging to the genus Faecalibacterium, resulting in identification of 15 candidate prophages, and validated the approach by demonstrating the activity of five prophages from four of the strains. The genomes of three active phages were identical or similar to those of known phages, while the other two active phages were not represented in the Viral RefSeq database. Four of the active phages possessed a diversity-generating retroelement (DGR), and one retroelement had two variable regions. DGRs of two phages were active at the time of the induction experiments, as evidenced by nucleotide variation in sequencing reads. We also predicted that the host range of two active phages may include multiple bacterial species. Finally, we noted that four phages were less prevalent in the metagenomes of inflammatory bowel disease patients compared to a general population cohort, a difference mainly explained by differences in the abundance of the host bacteria. Our study highlights the utility of prophage identification and induction for unraveling phage molecular mechanisms and ecological interactions.IMPORTANCEWhile hundreds of thousands of phage genomes have been discovered in metagenomics studies, only a few of these phages have been characterized experimentally. Here, we explore phage characterization through bioinformatic identification of prophages in genomes of cultured bacteria, followed by prophage induction. Using this approach, we detect the activity of five prophages in four strains of commensal gut bacteria Faecalibacterium. We further note that four of the prophages possess diversity-generating retroelements implicated in rapid mutation of phage genome loci associated with phage–host and phage–environment interactions and analyze the intricate patterns of retroelement activity. Our study highlights the potential of prophage characterization for elucidating complex molecular mechanisms employed by the phages.